2004
DOI: 10.1097/01.olq.0000109512.95959.ed
|View full text |Cite
|
Sign up to set email alerts
|

Rescreening for Gonorrhea and Chlamydial Infection Through the Mail

Abstract: Although not statistically significant, this study indicates that mailed rescreening could be a successful method to increase rescreening rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Geography: Two studies were conducted in the Netherlands,24 33 four in the UK,29 31 34 36 five in Australia9 10 27 28 35 and the remainder in the USA 22 23 25 26 30 32…”
Section: Resultsmentioning
confidence: 99%
“…Geography: Two studies were conducted in the Netherlands,24 33 four in the UK,29 31 34 36 five in Australia9 10 27 28 35 and the remainder in the USA 22 23 25 26 30 32…”
Section: Resultsmentioning
confidence: 99%
“…35 Similarly, in a randomized trial of methods to encourage rescreening for gonorrhea and chlamydia, only 32% of STD clinic clients returned for a retest. 36 In another study, systems to allow for chlamydia retesting through mail-in specimens yielded only a 23% response rate. 37 Many factors make the follow-up of patients with gonorrhea uniquely challenging.…”
Section: Discussionmentioning
confidence: 98%
“…In a small trial involving 122 patients from an urban STD clinic, 45% of women who were given the option of either rescreening in the clinic or home-based testing and 32% of those assigned to clinic-based rescreening were rescreened within 28 days of enrollment. 21 In women using long-acting reversible contraceptive methods, use of self-collected vaginal swabs significantly increased testing rates of Chlamydia infection and gonorrhea compared with clinic-based testing (56% compared with 25% during 12 months). 23 In high-risk young women, Cook et al reported that serial mailing of home-based kits significantly increased the use of Chlamydia and gonorrhea testing (82% in the home group and 61% in the clinic group had at least one test during the 2-year follow up).…”
Section: Discussionmentioning
confidence: 97%
“…Allowing women to choose between methods may help to increase overall rescreening adherence. 21 For patients who are motivated and can keep the specimen collection kit for 3 months, giving patients the kit in advance may be a better alternative than mailing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation